2016
DOI: 10.1021/acs.biochem.6b00322
|View full text |Cite
|
Sign up to set email alerts
|

Solution Nuclear Magnetic Resonance Studies of Sterol Carrier Protein 2 Like 2 (SCP2L2) Reveal the Insecticide Specific Structural Characteristics of SCP2 Proteins in Aedes aegypti Mosquitoes

Abstract: Sterol carrier protein 2 like 2 from Aedes aegypti (AeSCP2L2) plays an important role in lipid transport in mosquitoes for its routine metabolic processes. Repeated unsuccessful attempts to crystallize ligand free SCP2L2 prompted us to undertake nuclear magnetic resonance (NMR) spectroscopy to determine its three-dimensional structure. We report here the three-dimensional structures and dynamics of apo-AeSCP2L2 and its complex with palmitate. The (15)N heteronuclear single-quantum coherence spectrum of apo-AeS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…aegypti SCP-2 (AeSCP2), has been reported to be involved in cholesterol and fatty acid uptake in the midgut in both larval and adult mosquitoes [16]. A small number of studies have focused on developing new insecticides that prevent cholesterol biosynthesis targeting AeSCP2 [17][18][19]. Fifty seven compounds were identified in silico as possible inhibitors of the cholesterol-binding capacity of SCP-2 from the library of 16000 compounds [20].…”
Section: Introductionmentioning
confidence: 99%
“…aegypti SCP-2 (AeSCP2), has been reported to be involved in cholesterol and fatty acid uptake in the midgut in both larval and adult mosquitoes [16]. A small number of studies have focused on developing new insecticides that prevent cholesterol biosynthesis targeting AeSCP2 [17][18][19]. Fifty seven compounds were identified in silico as possible inhibitors of the cholesterol-binding capacity of SCP-2 from the library of 16000 compounds [20].…”
Section: Introductionmentioning
confidence: 99%
“…It highlights that a theoretically oriented chemical modification (in this case the introduction of the second phenyl ring) represents a rational design strategy for exploring opportunities of intermolecular hydrophobic interaction offered by the biomolecular target AeSCP-2. In this sense, it is interesting to observe that, recently, Singarapu et al 45 using solution NMR experiments showed that Sterol Carrier Protein 2 Like 2 (SCP2L2) can interact to palmitate through the hydrophobic residues Ile, Val, Leu, Met and Ala. Therefore, these results shed lights on the possibility that 1,2,4-oxadiazol acid derivatives presented in this work may also interact to this isoform of AeSCP2.…”
Section: Discussionmentioning
confidence: 51%
“…Simple equilibrium calculations demonstrate that partial displacement is difficult to explain by a single-site binding competition model; whereas partial displacement is accounted for by the more complex binding model proposed here. Second, the three-dimensional structure of the binding site, ligand location and orientation, and binding stoichiometry exhibit remarkable variability in the SCP2 family, as if it had evolved not only to cage most lipids but to carry more than one [2,9].…”
Section: Discussionmentioning
confidence: 99%
“…Among the cellular functions of SCP2 are: nonvesicular lipid transport and storage; membrane remodeling, lipid mediated signaling, isoprenoid and cholesterol metabolism, steroidogenesis, peroxisomal oxidation of branched and long-chain fatty acids, and cholesterol uptake [3][4][5][6][7][8][9]. Most of what is known about SCP2 concerns eukaryotic cells, whereas the functions of SCP2 in prokaryota are unexplored.…”
Section: Introductionmentioning
confidence: 99%